Docility, Obedience and Discipline: Towards Dirtier Leadership Studies?. Issue 1 (2nd January 2021) - Alvehus, Johan
ABSTRACT: Leadership is a popular term, among scholars and in general. It is romanticized and seems to cover everything and nothing. Its analytical value has therefore been questioned, and so has the very existence of leadership as a phenomenon. Here, based on the social psychology of GH Mead, I argue that leadership is a fundamental human phenomenon emanating from docility. By exploring this through the lens of three classic texts – Milgram's Obedience to Authority, Foucault's Discipline and Punish, and Taylor's The Principles of Scientific Management – I argue that processes that accomplish leadership are often not understood as leadership, but as something else, for example manipulation or management. More generally, I argue that leadership disappears as we identify the details of its manifestations, and from this I argue that leadership is a concept that denies its own ontological foundation. My conclusions suggest that leadership scholars and practitioners increasingly should draw attention to the choices involved in leadership processes and to practices commonly seen as not being about leadership – leadership studies will benefit from making the immaculate concept of leadership dirtier.